Case for diagnosis. Erythroderma as manifestation of hypereosinophilic syndrome - Maira Renata Merlotto; Lucas Oliveira Cantadori; Delmo Sakabe; Hélio Amante Miot (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Hypereosinophilic syndrome is defined as persistent eosinophilia (>1500/µL for more than six months) associated with organ involvement, excluding secondary causes. It is a rare, potentially lethal disease that should be considered in cutaneous conditions associated with hypereosinophilia. We report a case of erythroderma as a manifestation of hypereosinophilic syndrome. A 36-year-old male with no comorbidities presented progressive erythroderma, pruritus, peripheral neuropathy, and eosinophilia in the previous seven months. No mutations were found in FIP1L1/PDGFRA. Patient experienced rapid remission in response to oral prednisone and hydroxyurea. Cutaneous manifestations may be the only evidence of hypereosinophilic syndrome. Genotyping excludes myeloproliferative disease, thereby orienting treatment and prognosis.